2012
DOI: 10.5847/wjem.j.issn.1920-8642.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of ALOX5AP with ischemic stroke in eastern Chinese

Abstract: BACKGROUND: 5-lipoxygenase protein (ALOX5AP) has been recognized as a susceptibility gene for stroke and coronary artery diseases. The present study was to explore the role of this gene in the eastern Chinese patients with ischemic stroke. METHODS: Using a case-control design, we studied 658 patients with ischemic stroke and 704 unrelated population-based controls who were age-and sex-matched. The 658 patients were classified by the Trial of Org 10172 in Acute Stroke Treatment (TOAST). Two single-nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…T allele carriers were found to possess lower expression of ALOX5AP1 gene. It has been shown that there is an increased production of LTB4 in neutrophils from patients with a history of myocardial infarction compared to controls without history of myocardial infarction [17]. Expression studies have supported this where an increased expression of members of 5 lipoxygenase pathway including 5 lipoxygenase and ALOX5AP in atherosclerotic lesion at various stages of their development has been shown [28].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…T allele carriers were found to possess lower expression of ALOX5AP1 gene. It has been shown that there is an increased production of LTB4 in neutrophils from patients with a history of myocardial infarction compared to controls without history of myocardial infarction [17]. Expression studies have supported this where an increased expression of members of 5 lipoxygenase pathway including 5 lipoxygenase and ALOX5AP in atherosclerotic lesion at various stages of their development has been shown [28].…”
Section: Discussionmentioning
confidence: 91%
“…Expression studies have supported this where an increased expression of members of 5 lipoxygenase pathway including 5 lipoxygenase and ALOX5AP in atherosclerotic lesion at various stages of their development has been shown [28]. These studies suggest that chronic upregulation of leukotriene pathway may be harmful to the vasculature, in terms of atherosclerotic progression and plaque stability [17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The death rate in the two groups was approximately 6.7%, which was lower than the results of the NINDS test (17%) and ECASS test (22.4%). [ 6 , 11 ] Therefore, we consider that it is safe to perform rt-PA thrombolysis within 4.5–6 hours after the onset of ACI. García-Bermejo et al[ 19 ] has the same result.…”
Section: Discussionmentioning
confidence: 99%
“…The sooner the treatment begins, the better the efficacy would be. [ 6 , 7 ] Our department has a multidisciplinary team in collaboration with the departments of neurology, neurosurgery, radiology, and clinical laboratory in the second half of year 2008. In this study, cerebral stroke patients were primarily selected from the department of emergency medicine to enter the green channel.…”
Section: Introductionmentioning
confidence: 99%